Malezya'da İslam aile hukuku uygulamaları - Dindaroğlu, Zehra Betül (My University)
Bu çalışma Malezya’da İslam aile hukukuna dair uygulama örneklerini incelemektedir. Araştırmanın amacı, Malezya’nın kanun-şeriat ilişkisini nasıl konumlandırdığını anlamaya çalışmak ve aile hukuku alanındaki evlenme-boşanmaya dair çeşitli meseleleri inceleyerek İslam hukuk pratiğine etki eden örf ve mezhep algısı gibi unsurları tespit edebilmektir. Kültürel ve toplumsal olarak Şâfiî mezhebini benimseyen çok kültürlü, çok dinli, yer yer anaerkil öğelerin yer aldığı Malezya’da aile hukukuna dair yapılan içtihatlarda ve verilen kararlarda ülkenin dini algısı ile tarihsel-toplumsal-örfi-antropolojik yapısının ilişkisini ortaya koyabilmek amaçlanmıştır. Bu doğrultuda hukuk sosyolojisi, hukuk antropolojisi içeren bir yaklaşım benimsenmiş, özellikle eyaletlerin her birinin aile hukukunu incelerken mukayeseli hukuk metodundan faydalanılmıştır. Kanun metinleri ve uygulama örnekleri dokümantasyon tekniğiyle toplanmış, belgesel gözlem ve analize tabi tutulmuştur. Çalışmada aile hukuku uygulamaları üzerinden kanun-şeriat diyalogu incelenmiş, evlenme ve boşanmaların tescili konusunda şeriatın kanunun önüne geçirildiği gözlemlenmiş, Ehl-i kitapla evlilik hususunda Şâfiî mezhebinin katı görüşü tercih edilerek Malay ulusunun homojen kalması ve dini kültürünün korunması dikkate alınmış, mehir, mut‘a ve mal paylaşımı gibi konularda örfün hukuka etkisi tespit edilmiştir. Araştırma Malezya örneğinin aile hukuku pratiğinde günümüzde yüzleştiği problemlere nasıl cevaplar ürettiğini gözlemlemek ve böylelikle İslam hukukunu uygulanabilir hukuk seviyesinde incelemek açısından önem arz etmektedir.

This study examines the practical applications of Islamic family law in Malaysia. The aim of the research is to explore how Malaysia positions the relationship between statutory law and sharī‘ah, and to identify the influences of custom and sectarian interpretations on Islamic legal practices by analyzing various marriage and divorce-related issues in family law. In Malaysia, a multicultural and multi-religious society that culturally and socially adheres to the Shāfiʿī school of thought and incorporates occasional matrilineal elements, the aim has been to reveal the relationship between the country’s religious perceptions and its historical, social, customary, and anthropological structure as reflected in the jurisprudence and decisions concerning family law. Adopting an approach that integrates legal sociology and legal anthropology, the research employs a comparative law methodology to examine family law across Malaysia’s states. Legal texts and case examples were collected using documentation techniques and subjected to documentary observation and analysis. Through the lens of family law practices, the dialogue between statutory law and sharī‘ah is explored, revealing instances where sharī‘ah takes precedence over statutory law, particularly in the registration of marriages and divorces. The study also observes the adherence to the strict Shāfiʿī interpretation regarding marriages with People of the Book, aimed at preserving Malay national identity and cultural homogeneity, and identifies the influence of custom on legal matters such as mahr (dower), mutʿa (divorce compensation), and property distribution. This research is significant for understanding how the Malaysian example addresses contemporary challenges in family law practice and offers insights into the practical applicability of Islamic law in a modern legal framework.
The implementation and practices of Malaysian Islamic family law
Keywords: Aile hukuku; boşanma; divorce; Domestic relations; evlenme; family law; Malaysia; Malezya; marriage; Shariah courts; Şeriat mahkemeleri Malaysia